2017
DOI: 10.1101/187724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age, sex, and puberty related development of the corpus callosum: a multi-technique diffusion MRI study

Abstract: Purpose: The corpus callosum is integral to the central nervous system, and continually develops with age by virtue of increasing axon diameter and ongoing myelination. Magnetic resonance imaging (MRI) techniques offer a means to disentangle these two aspects of white matter development. We investigate the profile of microstructural metrics across the corpus callosum, and assess the impact of age, sex and pubertal development on these processes. Methods:This study made use of two independent paediatric populat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Indeed, we observed that mean AFD of the left SLF was significantly reduced in those with DCD, with along tract analysis suggesting that this group difference was accentuated in those portions of the SLF immediately anterior to the arcuate fasciculus. AFD provides a metric of intra-axonal volume fraction ( Raffelt et al, 2012a , Raffelt et al, 2012b ), with higher values potentially reflecting increased axon diameter or local axon count ( Genc et al, 2018 ). Accordingly, our data suggest that individuals with DCD may have decreased axon diameter or count in the left SLF relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed that mean AFD of the left SLF was significantly reduced in those with DCD, with along tract analysis suggesting that this group difference was accentuated in those portions of the SLF immediately anterior to the arcuate fasciculus. AFD provides a metric of intra-axonal volume fraction ( Raffelt et al, 2012a , Raffelt et al, 2012b ), with higher values potentially reflecting increased axon diameter or local axon count ( Genc et al, 2018 ). Accordingly, our data suggest that individuals with DCD may have decreased axon diameter or count in the left SLF relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…CSF). NODDI-derived measures have appear to be more closely associated with age in youth than standard DTI metrics ( Chang et al, 2015 ; Deligianni et al, 2016 ; Eaton-Rosen et al, 2015 ; Genc et al, 2018 ; Kodiweera & Wu, 2016 ; Mah et al, 2017 ; Nazeri et al, 2015 ; Ota et al, 2017 ). “Signal” based methods use quantitative, efficient and robust mathematical models to describe molecular displacements in brain white matter.…”
Section: Future Directions and Ongoing Challenges In Pediatric Dmrimentioning
confidence: 99%
“…Sex differences in relative size, connectivity, and function have been well characterized in several brain regions (Kaczkurkin et al., 2019); one such region is the corpus callosum (CC), developing in a sex‐specific manner across the lifespan (Genc et al., 2018; Lebel et al., 2012; F. Liu et al., 2010; Luders et al., 2011; Schmithorst et al., 2008). The CC is the largest white matter (WM) structure in the human brain, composed of highly organized commissural projection neurons that facilitate interhemispheric communication, mediating high‐level association and lateralized functional processes (Fame et al., 2011; van der Knaap & van der Ham, 2011).…”
Section: Introductionmentioning
confidence: 99%